The `beautiful game` and its dilemmas: sports migration, `Brazilianness` and `race` - De Oliveira Filho, J. H. (Soccer & Society, 2022)
The relationship between sports, especially football, Brazilian national identity, and `race`, has received considerable attention. The hyper-visibility of football, however, obscures the relationship between Brazilian identity with another sport that was partially `invented` in Brazil: futsal. This paper examines migrant Brazilian football and futsal athletes, through an analysis of their life-histories. The study combines life-histories, a re-construction of long-term historical processes that inform and condition the specificity of Brazilian identity, and media discourses to construct a novel perspective on the relationship between `Brazilianness` and sports.